Análise experimental do efeito do ângulo de injeção de gás em um escoamento vertical ascendente de líquido - Guerra, Luiz Alberto de Oliveira (2017)
Evaluates the effect of the gas injection angle in a upward vertical liquid flow, regarding the bubble size and shape distributions, as well as liquid velocity profile, both in the injection area. The experiments are carried in a 44 mm acrylic vertical pipe, in which water flows and air is injected through an angled device, in relation to the main liquid stream. Three different injection angles are used, 45° countercurrent, perpendicular and 45° in favor of the main stream. A variety of liquid and air injection flow rates are applied, as well as two injection orifices with different diameters. Bubbles are identified by the shadow sizing technique and velocity profiles by the particle image velocimetry technique. Main conclusions are: (i) bubble size distribution depends on gas injection angle, as a function of injection flow rate; (ii) bubble shape distribution varies with its equivalent diameter, being not affected by gas injection angle, however; (iii) injection orifice size affects bubble size and shape distributions; (iv) liquid vertical velocity profiles, specifically their velocity peak amplitude and location, are influenced by gas injection angle.